The impact of airport road wayfinding on senior driver behaviour - Anuar, Nur Khairiel; Sabar, Rohafiz; Pagliari, Romano; Moxon, Richard (UUM College of Business, Universiti Utara Malaysia, 2017)
The purpose of this study was to measure the impacts of airport road access design and wayfinding systems on senior driver performances. A car driving simulator was used to model scenarios of differing wayfinding complexity and road design. Three scenario types were designed consisting of 3.8 miles of airport road (i.e. approximately 4 minutes driving to complete each scenario). Experienced car drivers were asked to drive simulated routes.Forty drivers in the age ranges: 50 to 54, 55 to 59 and those aged over 60 were selected to perform the study.Participants drove for approximately 20 minutes to complete the simulated driving. The driver performance was compared between age groups. Results were analysed by Mean,Standard Deviation and ANOVA Test, and discussed with reference to the use of the driving simulator. The ANOVA results showed that in comparison of senior drivers‟ age group, there is a low impact between driving behaviour and road safety on airport road access wayfinding design.